The quickie : [compact disc, unabridged] : a novel - Patterson, James, 1947- (Hatchette Audio, 2007)
When NYPD officer, Lauren Stillwell, discovers her husband coming out of a hotel with another woman she decides to beat him at his own game but her revenge goes awry.